Improvement of Intangible Assets Accounting and Auditing - Yuldashevna Umida Rozmatovna. (Zien Journals, 2022)
The following article reviews current problems of improving accounting and inventory of intangible assets in the organization. It reveals some measures to prevent financial loses and save incomes of organization properties.
Keywords: accounting; intangible assets; alienation; inventory